TRNA methyltransferase homologue gene TRMT10A mutation in young adult‐onset diabetes with intellectual disability, microcephaly and epilepsy. Issue 9 (September 2016) - Yew, T. W.; McCreight, L.; Colclough, K.; Ellard, S.; Pearson, E. R.
Abstract: Background: A syndrome of young‐onset diabetes mellitus associated with microcephaly, epilepsy and intellectual disability caused by mutations in the tRNA methyltransferase 10 homologue A ( TRMT10A ) gene has recently been described. Case report: We report two siblings from the fourth family reported to have diabetes mellitus as a result of a TRMT10A mutation. A homozygous nonsense mutation p.Glu27Ter in TRMT10A was identified using targeted next‐generation sequencing and confirmed by PCR/Sanger sequencing. Diabetes was diagnosed while the subjects were in their 20s and was characterized by insulin resistance. Epilepsy and intellectual disability were features in common. Mild microcephaly was present at birth but their final head circumferences were normal. Conclusion: Our report provides independent confirmation of the role of TRMT10A mutations in this syndrome and expands its phenotypic description. TRMT10A sequencing should be considered in children or adults with young‐onset diabetes who have a history of intellectual disability, microcephaly and epilepsy. This report also shows the advantages of using a targeted panel to identify previously unsuspected monogenic diabetes among young‐onset non‐insulin‐dependent diabetes in the absence of obesity and autoimmunity. What's new?: This report describes the fourth family reported to have diabetes mellitus caused by a mutation in the TRMT10A gene. In contrast to the previous families, the diabetes mellitus in the patients we describe was diagnosed after 20 years of age, and at diagnosis they had only mild learning disability and epilepsy with minimal other clinical features. TRMT10A sequencing should be considered in children or adults with young‐onset diabetes who have a history of intellectual disability, microcephaly and epilepsy. A targeted panel may be useful to identify previously unsuspected monogenic diabetes among individuals with young‐onset diabetes.